Discovery of PET radiopharmaceuticals at the academia-industry interface. (November 2017) - Bernard-Gauthier, Vadim; Collier, Thomas L.; Liang, Steven H.; Vasdev, Neil
Abstract : Project-specific collaborations between academia and pharmaceutical partners are a growing phenomenon within molecular imaging and in particular in the positron emission tomography (PET) radiopharmaceutical community. This cultural shift can be attributed in part to decreased public funding in academia in conjunction with the increased reliance on outsourcing of chemistry, radiochemistry, pharmacology and molecular imaging studies by the pharmaceutical industry. This account highlights some of our personal experiences working with industrial partners to develop new PET radiochemistry methodologies for drug discovery and neuro-PET research studies. These symbiotic academic-industrial partnerships have not only led to novel radiotracers for new targets but also to the application of new carbon-11 and fluorine-18 labeling methodologies and technologies to label previously unprecedented compounds for in vivo evaluations.